2012
DOI: 10.1093/abbs/gms090
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of a <italic>Bombyx mori</italic> cocoonase: potential application for silk degumming

Abstract: Cocoon, a shelter for larva development to silk moth, contains the fibrous protein fibroin, which is coated by the globular protein sericin. Emergence of the silk moth requires the action of cocoonase, a protease secreted by the pupa. The full-length prococoonase cDNA, with 780 bp open reading frame encoding 260 amino acids, was cloned by reverse transcription from total RNA of the head of 6-dayold Thai-silk Bombyx mori pupa. Only the gene fragment lacking the propeptide encoding sequence was successfully expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 13 publications
3
11
1
Order By: Relevance
“…The fibroin damage analysis, weight loss, SEM analysis and OPA assay experiments supported the same result: cocoonase had no effect on fibroin fiber. The data coincided with other degumming proteolytic enzymes such as the bromelain from pineapple fruit or protease from Bacillus subtilis C4 isolated from degumming wastewater (data not shown) or recombinant cocoonase from Rodbumrer et al 21 This current study clearly demonstrated that the cocoonase had no effect on fibroin fiber. The catalytic function of cocoonase in the silkworm during developmental stages needs to be further characterized.…”
Section: Degumming Ratio Of Recombinant Bmcocsupporting
confidence: 89%
See 4 more Smart Citations
“…The fibroin damage analysis, weight loss, SEM analysis and OPA assay experiments supported the same result: cocoonase had no effect on fibroin fiber. The data coincided with other degumming proteolytic enzymes such as the bromelain from pineapple fruit or protease from Bacillus subtilis C4 isolated from degumming wastewater (data not shown) or recombinant cocoonase from Rodbumrer et al 21 This current study clearly demonstrated that the cocoonase had no effect on fibroin fiber. The catalytic function of cocoonase in the silkworm during developmental stages needs to be further characterized.…”
Section: Degumming Ratio Of Recombinant Bmcocsupporting
confidence: 89%
“…More than 90% of purified recombinant BmCoc was recovered from yeast culture medium and retained activity for as long as 1 h of incubation at pH 8 and 40 ∘ C. Obtaining recombinant BmCoc expression was enhanced by removing the signal peptide at the N-terminus of the protein. The data obtained in this study are closely related to the report of Rodbumrer et al, 21 which expressed B. mori cocoonase using pPICz-A expression vector with minor adjustments in vector construction, i.e. size of expressed mature cocoonase with the removal of a signal protein and addition of histidine tag for protein purification.…”
Section: Expression and Purification Of Recombinant Bmcoc In P Pastorissupporting
confidence: 86%
See 3 more Smart Citations